2011
DOI: 10.1245/s10434-011-2105-5
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Metastatic Lymph Node Ratio on Stimulated Thyroglobulin Levels in Papillary Thyroid Carcinoma after Prophylactic Unilateral Central Neck Dissection

Abstract: BackgroundPrognostic significance of metastatic central lymph node ratio (CLNR) in papillary thyroid carcinoma (PTC) remains unknown. Because postsurgical detectable stimulated thyroglobulin (DsTg) after radioiodine ablation may imply persistent or recurrent disease, we evaluated the association between CLNR and rate of DsTg in patients with PTC who underwent unilateral prophylactic central neck dissection.MethodsTo be eligible for analysis, the prophylactic central neck dissection specimen had to contain ≥3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
(25 reference statements)
2
36
2
Order By: Relevance
“…Recurrence-free survival rate according to pathological T stage was 96.7% in T1, 76.5% in T2, and 84.6% in T3, and it seems that pathological T staging is not enough to predict prognosis (hazard ratio 1.53, 95% CI 0.94 to 2.51, PZ0.090). This is not consistent with the previous data (1,10,11,12) and we think that patient selection bias might have led to this conclusion, as only those with tumor size O1 cm were analyzed. Patients with tumor size !1 cm showed overall excellent prognosis and it was not meaningful to analyze the impact of central neck LN metastases.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Recurrence-free survival rate according to pathological T stage was 96.7% in T1, 76.5% in T2, and 84.6% in T3, and it seems that pathological T staging is not enough to predict prognosis (hazard ratio 1.53, 95% CI 0.94 to 2.51, PZ0.090). This is not consistent with the previous data (1,10,11,12) and we think that patient selection bias might have led to this conclusion, as only those with tumor size O1 cm were analyzed. Patients with tumor size !1 cm showed overall excellent prognosis and it was not meaningful to analyze the impact of central neck LN metastases.…”
Section: Discussioncontrasting
confidence: 92%
“…Several studies also suggested that larger size or higher number of metastatic LNs in PTC is associated with poorer outcomes (1,10,11,12,13). A recent review suggested new risk factors that modify standard N1 risk of recurrence such as clinical status, size, number, or presence of extranodal extension of metastatic lesions in LNs (14).…”
Section: Introductionmentioning
confidence: 99%
“…4,11 Recent data suggest that in addition to LN location, LN characteristics such as maximal size, number, ratio, and ENS are also prognostic. 510 Age at diagnosis is uniquely critical in the staging of differentiated thyroid cancer, and in this series of 438 PTC patients with lateral neck disease, we report LN characteristics that are predictive of outcome in two age cohorts of patients, those <45 years old and those ≥45 years old. In both age groups, both number of positive LNs >10 and LN burden >17 % (which equated to 1 positive node per 6 removed) were predictive for recurrence.…”
Section: Discussionmentioning
confidence: 87%
“…Others have observed central compartment LN burden to be predictive of postoperative thyroglobulin levels as well as recurrence. 5,6 Our study specifically focuses on the prognostic significance of lateral compartment LN characteristics. Our data show that younger patients with LN burden >17 % were 4.8 times ( p < 0.001) and older patients 2.7 times ( p < 0.02) more likely to develop disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation